THE EFFECT OF THE RISK MANAGEMENT IMPLEMENTATION ON STOCK RETURNS IN THE BANKING INDUSTRY LISTED ON THE INDONESIA STOCK EXCHANGE 2016-2019 PERIOD - Marmaini, Fabian Firjun; Sudjono, Sudjono; Badawi Saluy, Ahmad (Dinasti Publisher, 2021)
The aim of this research was to determine the conditions of the application of risk management for commercial banks in Indonesia and to determine the effect of the application of risk management on banking stock price returns based on model 1, model 2, model 3 and determine the best model for stock price return estimation. In measuring the level of risk management implementation in banking, two approaches are used, namely trend analysis and empirical analysis. The following conclusions can be drawn: (1) In model 1, trends The movement of the NETIM variable in one year from period one (March) to period four (December) always goes up and down at the beginning of the year. next. The NONIM variable, the movement in the quarterly period at the beginning tends to be flat, starting to rise in the December 2016 period, while the movement from year to year is not very volatile. (2) In model 2, the trend of the movement of the AVERAGE variable during the 2016-2019 period tends to increase as indicated by the trend line . (3) In model 3, trends The movement of the PRIN1 and PRIN2 variables from year to year during the study period seems to fluctuate (4) Based on the results of the comparison of the four regression estimation models, it can be concluded that the first model is the best model in explain the variation of the movement of the return variable.